Exposure to nanoplastics and nanomaterials either single and combined affects the gill-associated microbiome of the Antarctic soft-shelled clam Laternula elliptica - Rodolfo Rondon; Céline Cosseau; Elisa Bergami; César A. Cárdenas; Carolina Pérez-Toledo; Diego Alvarez; Jacqueline Aldridge; Alejandro Font; Ignacio Garrido; Francisco Santa Cruz; Garance Perrois; Teresa Balbi; et al. (Marine Environmental Research, 2024)

Correction: Microbiome profile of the Antarctic clam Laternula elliptica - Marcelo González-Aravena; Garance Perrois; Alejandro Font; César A. Cárdenas; Rodolfo Rondon (Brazilian Journal of Microbiology, 2024)

Microbiome profile of the Antarctic clam Laternula elliptica - Marcelo González-Aravena; Garance Perrois; Alejandro Font; César A. Cárdenas; Rodolfo Rondon (Brazilian Journal of Microbiology, 2024)

Low Transcriptomic Plasticity of Antarctic Giant Isopod Glyptonotus antarcticus Juveniles Exposed to Acute Thermal Stress - Marcelo González-Aravena; Rodolfo Rondon; Alejandro Font; César A. Cárdenas; Jean-Yves Toullec; Erwan Corre; Kurt Paschke (Frontiers in Marine Science, 2021)
The Western Antarctic Peninsula (WAP) is among the areas of the planet showing some of the most significant increases in air and water temperature. It is projected that increasing temperature will modulate coastal ecosystems at species ecological performance and molecular composition. The main way that the organisms can cope with large thermal variation is by having a reversible phenotypic plasticity, which provides the organisms with a compensatory physiological response when facing challenging conditions. The giant Antarctic isopod Glyptonotus antarcticus is one of most common species in Antarctic waters. This species has a larval development inside of the maternal marsupium, where juveniles have a short period to acclimate to environmental conditions after birth. In this sense, we hypothesize that juveniles exposed to unusual temperature increases even for short periods, would not respond adequately showing a narrow phenotypic plasticity. We experimentally assessed if early juveniles of G. antarcticus have the molecular plasticity when exposed to increased temperature at 5°C during 1, 6, 12 and 24 h. Sequenced libraries were compared between control (0°C) and each experimental treatment to detect differentially expressed transcripts. The main molecular pathways affected by thermal stress were antioxidant, proteases, endopeptidases and ubiquination transcripts which were up-regulated and mitochondrial respiratory chain, cuticle, cytoskeleton and a molt transcript which were down-regulated. Regarding the HSP transcript, only 3 were up-regulated at least in two points of the stress kinetic, without classical Hsp70 and Hsp90 transcripts. This study shows that juveniles of G. antarcticus do not show molecular phenotypic plasticity to cope with acute short-term heat stress, even for one or few hours of exposure with an absence of an eco-physiological capacity to respond. This may have consequences at the ecological population level, showing a reduced individual ability to survive decreasing population recruitment.

Detection of peroxiredoxin-like protein in Antarctic sea urchin (Sterechinus neumayeri) under heat stress and induced with pathogen-associated molecular pattern from Vibrio anguillarum - Byron Morales-Lange; Marcelo González-Aravena; Alejandro Font; Fanny Guzmán; Luis Mercado (Polar Biology, 2018)